2007
DOI: 10.1007/s10286-007-0441-0
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training improves cardiovascular and autonomic profiles in HIV

Abstract: Augmentations in arterial compliance and baroreflex sensitivity associated with fitness portent an improved CV and autonomic profile for HIV-positive individuals. Physical activity may be an adjuvant method to enhance the overall vascular health in HIV-compromised individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
1
9

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 55 publications
3
17
1
9
Order By: Relevance
“…These HRV results are in line with what is known from studies in athletes indicating that regular exercise (higher VO 2max ) benefits the resting ANS by increasing HRV, lowering the sympathetic influence on the heart and increasing the parasympathetic influence (Nagai et al, 2004;Spierer et al, 2007;Gilder and Ramsbottom, 2008). It also confirms that only a limited number of HRV indicators, based on weak associations in the supine position, could perhaps be used to estimate VO2max. However, this study also clearly demonstrates the novel relationship between HRV indicators and indicators of physical fitness during an orthostatic stressor.…”
Section: Hrvsupporting
confidence: 89%
See 1 more Smart Citation
“…These HRV results are in line with what is known from studies in athletes indicating that regular exercise (higher VO 2max ) benefits the resting ANS by increasing HRV, lowering the sympathetic influence on the heart and increasing the parasympathetic influence (Nagai et al, 2004;Spierer et al, 2007;Gilder and Ramsbottom, 2008). It also confirms that only a limited number of HRV indicators, based on weak associations in the supine position, could perhaps be used to estimate VO2max. However, this study also clearly demonstrates the novel relationship between HRV indicators and indicators of physical fitness during an orthostatic stressor.…”
Section: Hrvsupporting
confidence: 89%
“…According to these negative correlations between VO 2max and the two HRV indicators, supine sympathetic nervous system activity is lower in fitter individuals. These results are supported by several published studies (Nagai et al, 2004;Spierer et al, 2007;Gilder and Ramsbottom, 2008). No significant correlations were found between supine HRV indicators and O 2 pulse max or peak treadmill speed.…”
supporting
confidence: 84%
“…4,8,[10][11][12][13]15,17,18,[19][20][21]25,27,[30][31][32][34][35][36]38,39,45,47 The results of 10 articles on ANS response measured during exercise are shown in Table I. Some authors expressed concern about the measurement of spectral analysis of HRV during exercise, while others reported increases (↑), decreases (↓) and no changes in variability indicators (↔) of sympathetic (SNS) and parasympathetic (PNS) influence.…”
Section: Resultsmentioning
confidence: 99%
“…One study 15 reported no change in baseline BRS and HRV values after a 16-week fitness programme, while another found increased BRS when comparing fitness levels. 47 Aubert et al also found no evidence of significant changes in resting autonomic modulation of the sinus node after a low-volume, moderate-intensity 1-year exercise programme. 4 Comparing 11 young sedentary participants and 10 endurance-trained cyclists Martinelli et al found no difference in power-spectral components of HRV at rest.…”
Section: Discussionmentioning
confidence: 95%
“…In other studies that have shown a decreased BPV (and increased baroreceptor sensitivity) after prolonged training, participants were either all over the age of 40 or had comorbid illnesses. [23] As such it is plausible that in a young, healthy population, good autonomic modulation is preserved and the margin for improvement with exercise will always be limited and seldom be significant. Conversely, in an elderly population or in a population with comorbidities affecting the cardiovascular system, such as diabetes or recent myocardial infarction, sustained exercise causes numerous beneficial changes to vasculature and neural modulation, which cumulatively result in a significant decrease in BPV post intervention.…”
Section: Discussionmentioning
confidence: 99%